Hukum-Hukum Gas Ideal - Meyrida Riana; Anggini Anggini (Pentagon : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
The simplest gas and approaching the simplest properties of a true gas is an ideal gas. Ideal gases satisfy the ordinary gas equation, while real gases do not always satisfy the ideal gas equation. Gas laws such as Boyle's Law, Charles' Law, and Gay Lusaac's Law, show the relationships between macroscopic units of various processes and formulations.This research is a type of literature review research by looking for theoretical references that are relevant to the cases or problems found.The results of Boyle's experiments stated that if the temperature of a gas in a closed vessel is kept constant, the gas pressure will be inversely proportional to its volume. Gay-Lusaac's law states that the volume of gas in a closed vessel is maintained constant, the gas pressure will be proportional to its absolute temperature. Charles's law states that at constant pressure, the volume of an ideal gas of a certain mass is directly proportional to its temperature. An ideal gas is a concept in physics which assumes that a gas consists of very small particles with zero volume, do not interact with each other, and move randomly in a closed container. This concept also assumes that collisions between gas particles and the walls of the container are elastic, meaning that kinetic energy is maintained in each collision.